Evaluasi dan Perbaikan Desain Antarmuka Pengguna Website DPD PPNI Kabupaten Malang menggunakan Pendekatan Design Thinking - Gitahayu Pradipta; Retno Indah Rokhmawati; Intan Sartika Eris Maghfiroh (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
DPD PPNI Malang Regency is one of the organizations that oversees the nursing profession in the Malang Regency area. Based on the results of a brief interview with one of the administrators, there were problems with the website and he wanted to integrate the website with membership and cooperative services. Therefore, to improve the website that is owned, a user interface design is needed. In this study, using the Design Thinking approach in the improvement process. There are 5 stages that must be carried out, namely empathize, define, ideate, prototype, and test. The results of this study are in the form of user interface designs for the admin and member user categories. For the admin user category, there is a feature to verify submissions for membership requirements and cooperative transactions. As for the member user category, there is a feature to view company profiles, catalogs of goods sold in cooperatives, submit membership requirements, and cooperative transactions. The design that has been made is then evaluated using the Usability Testing and Single Ease Question (SEQ) methods which produce quantitative and qualitative data. Evaluation results using Usability Testing obtained several suggestions from respondents. From the results of the evaluation using SEQ, a score of 6.5 was obtained from a scale range of 7 for the admin and member user categories.